2018
DOI: 10.1585/pfr.13.3403015
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of High-Frequency Magnetosonic Waves Excited by Energetic Ions in Association with Ion Cyclotron Emission

Abstract: Instabilities of high-frequency magnetosonic waves caused by energetic ions with a ring-like velocity distribution are studied with a one-dimensional electromagnetic particle code which simulates self-consistently the full ion and electron dynamics. It is shown that the magnetosonic waves with frequencies slightly smaller than the lower-hybrid resonance frequency rapidly grow to large amplitudes, in addition to electromagnetic emissions near the ion cyclotron frequency and its harmonics. The frequency of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
(13 reference statements)
1
11
0
Order By: Relevance
“…In this data set, the perpendicular beam species was deuterium and the magnetic axis was fixed at R = 3.6 m. The absolute value of magnetic field strength on axis was between 2.705 and 2.85 T. The frequency increases with the line-averaged electron density. In order to simulate RF waves excited by energetic ions, Particle In Cell (PIC) simulation was conducted with the following assumptions [11].…”
Section: Rf Wave With the Frequency Of Lhw Rangementioning
confidence: 99%
“…In this data set, the perpendicular beam species was deuterium and the magnetic axis was fixed at R = 3.6 m. The absolute value of magnetic field strength on axis was between 2.705 and 2.85 T. The frequency increases with the line-averaged electron density. In order to simulate RF waves excited by energetic ions, Particle In Cell (PIC) simulation was conducted with the following assumptions [11].…”
Section: Rf Wave With the Frequency Of Lhw Rangementioning
confidence: 99%
“…9,10) When the energetic-ion ring speed is much smaller than the 1/20 Alfvén speed, electrostatic lower hybrid waves (LHWs) are excited. 11,12) Here, we define the LHWs as electrostatic waves around the lower hybrid resonance frequency ω LH , which is given by…”
Section: Introductionmentioning
confidence: 99%
“…2, the simulation code treats both the electrostatic and the electromagnetic fields by calculating the full Maxwell's equation. We pay attention to magnetic fluctuations shown in the simulation, as in the previous paper [8].…”
Section: Simulation Model and Parametersmentioning
confidence: 99%
“…In ref. [8], we investigated the linear and nonlinear evolution of instabilities due to energetic ions produced by the perpendicular NBI, assuming that the energetic ions have a ring-like distribution in the velocity space perpendicular to the magnetic field. It was shown that in addition to electromagnetic emissions near the ion cyclotron frequency and its harmonics, the high-frequency magnetosonic waves with frequencies slightly smaller than ω LH grow to large amplitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation